Collaborative Leadership in the Development of Integrated Land Data in Indonesia: A Systematic Literature Review - Mansur Fahmi; Nur Wening (Sekolah Tinggi Pertanahan Nasional, 2026)
This study examines the role of collaborative leadership in the development of integrated land data through a Systematic Literature Review (SLR) of 31 selected scholarly articles published between 2012 and 2025. The findings indicate that the successful development of integrated land data depends not only on technological advancement but also on the capacity of cross-sectoral leadership to foster coordination, institutional interoperability, and adaptive data governance. Standards and frameworks such as the Land Administration Domain Model (LADM), Indonesia's One Map Policy, and the Fit-for-Purpose Land Administration (FFP-LA) approach provide essential foundations for supporting land data integration in Indonesia. The study's principal finding confirms that collaborative leadership serves as the primary driving force behind the development of an integrated land data system by strengthening data governance, promoting standardization, and facilitating the adoption of technological innovation. Based on these findings, the study proposes a conceptual framework that positions collaborative leadership as the entry point for aligning data governance, international standards, and technological innovation to achieve an interoperable and sustainable land data system. The study recommends strengthening collaborative governance, enhancing institutional integration, and developing human resource capacity to support a sustainable national land administration system.